Java in a nutshell - Evans, Benjamin J. (In a nutshell (O'Reilly & Associates), 2019)
"This updated edition of Java in a Nutshell not only helps experienced Java programmers get the most out of Java versions 9 through 11, its also a learning path for new developers. Chock full of examples that demonstrate how to take complete advantage of modern Java APIs and development best practices, this thoroughly revised book includes new material on Java Concurrency Utilities. The books first section provides a fast-paced, no-fluff introduction to the Java programming language and the core runtime aspects of the Java platform. The second section is a reference to core concepts and APIs that explains how to perform real programming work in the Java environment. Get up to speed on language details, including Java 9-11 changes Learn object-oriented programming, using basic Java syntax Explore generics, enumerations, annotations, and lambda expressions Understand basic techniques used in object-oriented design Examine concurrency and memory, and how theyre intertwined Work with Java collections and handle common data formats Delve into Javas latest I/O APIs, including asynchronous channels Use Nashorn to execute JavaScript on the Java Virtual Machine Become familiar with development tools in OpenJDK."--Back cover.